1996
DOI: 10.1063/1.116580
|View full text |Cite
|
Sign up to set email alerts
|

In situ, atomic force microscope studies of the evolution of InAs three-dimensional islands on GaAs(001)

Abstract: The size evolution of molecular beam epitaxy-grown strained InAs three-dimensional (3D) islands on GaAs(001) is examined using in situ ultrahigh vacuum atomic force microscopy. Remarkably, just after the initiation of well-formed 3D islands at ∼1.57 ML InAs deposition, the lateral size dispersion and average value are found to first increase drastically with the smallest amount (∼0.05 ML) of additional InAs deposition and then decrease and saturate, indicating the onset of a natural tendency for size equalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
110
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(127 citation statements)
references
References 1 publication
15
110
1
1
Order By: Relevance
“…It has also been observed that the size distribution of the 3D islands is very narrow. The above observations have been reported for the growth of Ge on Si͑100͒, 2,4,[11][12][13][14][15][16] InAs on GaAs͑100͒, [17][18][19][20][21][22] InGaAs on GaAs, 3,[23][24][25] and InP on In 0.5 Ga 0.5 P. 26 In all cases the lattice misfit is positive and very large ͑4.2, 7.2, and Ϸ3.8 % for Ge/Si, InAs/GaAs, and InP/In 0.5 Ga 0.5 P, respectively͒ for semiconductor materials, which are characterized by directional and brittle chemical bonds. The only exception to the authors' knowledge is the system PbSe/PbTe͑111͒ in which the misfit is negative (Ϫ5.5%) and the overlayer is expanded.…”
Section: Introductionsupporting
confidence: 49%
“…It has also been observed that the size distribution of the 3D islands is very narrow. The above observations have been reported for the growth of Ge on Si͑100͒, 2,4,[11][12][13][14][15][16] InAs on GaAs͑100͒, [17][18][19][20][21][22] InGaAs on GaAs, 3,[23][24][25] and InP on In 0.5 Ga 0.5 P. 26 In all cases the lattice misfit is positive and very large ͑4.2, 7.2, and Ϸ3.8 % for Ge/Si, InAs/GaAs, and InP/In 0.5 Ga 0.5 P, respectively͒ for semiconductor materials, which are characterized by directional and brittle chemical bonds. The only exception to the authors' knowledge is the system PbSe/PbTe͑111͒ in which the misfit is negative (Ϫ5.5%) and the overlayer is expanded.…”
Section: Introductionsupporting
confidence: 49%
“…There is oneto-one In nanocrystal to InAs island correspondence, because the initial and final densities match. In accordance with previous reports [10], the InAs islands flatten and develop a local wetting layer elongated along [0][1][2][3][4][5][6][7][8][9][10][11]. For the symmetric In nanocrystals on the c(4 x 4) reconstructed surface ( Fig.…”
Section: Resultssupporting
confidence: 73%
“…Such applications require reproducible and well controllable means of obtaining low-density QDs, as a single QD is the basic building block of the above mentioned devices. Low-density InAs/GaAs QDs can be obtained by molecular beam epitaxy (MBE) using the Stransld-Krastanov (SK) growth mode and small InAs coverage above the critical thickness [6] or extremely small growth rates [7]. An alternative, yet so far widely unexplored route to achieve this is to use droplet epitaxy [8][9][10], where one first deposits metallic liquid In droplets or, in our case epitaxial In nanocrystals and afterwards recrystalizes them under As flux.…”
Section: Introductionmentioning
confidence: 99%
“…The geometry of a quantum dot grown by molecular beam epitaxy varies widely with the growth condition. [52][53][54] Based on the experimentally achievable geometries, we model a lensshaped self-assembled InAs dot with diameter 15 nm and height 6 nm, as shown in Fig. 1.…”
Section: ͑2͒mentioning
confidence: 99%